Sparkle Through Speech 3.0. Digital dialogue: mastering communication skills / Nur Afiqah Ab Latif , Marni Jamil and Noraziah Mohd Amin - Ab Latif, Nur Afiqah; Jamil, Marni; Mohd Amin, Noraziah (Academy of Language Studies, 2024)
The Sparkle Through Speech (STS) programme is a specialised initiative designed for school students to enhance their language skills, specifically communicating in English, with confidence. It is organised by the Academy of Language Studies (APB), Universiti Teknologi MARA, Pulau Pinang Branch (UiTMCPP). The STS programme has progressed through three iterations as university social responsibility (USR) initiatives, namely STS 1.0, STS 2.0, and STS 3.0, beginning with the initial STS 1.0 launched on 28 August 2023, with a focus on enhancing public speaking skills in English. Building on its success, STS 2.0, then held on 27 December 2023, at the Tun Abdul Razak Library (PTAR), UiTMCPP, introduced additional activities such as learning German and French, attracting 35 participants aged 6 to 12. STS 3.0, the latest iteration, offered meticulously designed modules that integrate digital technology to effectively communicate ideas, aligning with the latest communication needs. The objectives of the STS 3.0 programme include enhancing participants' communication confidence, fostering creative thinking in technology use for learning, exposing participants to positive aspects of podcasting, and cultivating leadership, teamwork, and problem-solving skills. The organising committee, led by Miss Marni Jamil as the Programme Director, 7 APB lecturers (Nur Afiqah Ab. Latif, Noraziah Mohd Amin, Anwar Farhan Mohd Marzaini, Nur Fatin Shahmina Mohd Fauzey, Muhamad Usamah Mohd Ridzuan, Raja Rosila Raja Berahim and Wan Noorli Razali) as the committee members and facilitators, 7 UiTMCPP students and 1 teacher from MRSM Transkrian as the facilitators, aims to achieve these objectives with the support of the UiTMCPP Administration Division. The programme, themed "Digital Dialogue: Mastering Communication Skills," was organised by the Academy of Language Studies (APB), UiTMCPP and took place on 14 and 15 February 2024, at the Tun Abdul Razak Library, (PTAR) UiTMCPP. 45 participants aged 8 to 12 registered to join the programme.